Virtual reality and affective learning in commemorative history teaching: Effects of immersive technology and generative learning activities - Miriam Mulders; Kristian H. Träg; Lilly Kaninski; Lara Kirner; Michael Kerres (Journal of Research on Technology in Education, 2025)
Learning with virtual reality (VR) can be highly motivating and conducive for cognitive and affective learning outcomes. For commemorative history education, VR enables novel experiences of testimonies co-created by survivors, witnesses, and museums. VR technologies allow learners to feel immediacy and an emotional connection to digitally reconstructed spaces and events of the past. While VR has proven to enhance affective learning outcomes by provoking emotions, interest, or motivation, its perceptual richness may also lead to distraction and cognitive overload. Generative learning activities can alleviate some of the limitations of learning with VR by helping learners to focus on the learning material. This study examines a highly engaging and historical immersive VR application and thereby investigates the effectiveness of the generative learning activities of self-explaining and drawing. Seventy-four undergraduate students explored a three-dimensional representation of the room where Anne Frank, a Jewish girl, was hiding during World War II. For the two experimental conditions, students had to either create drawings of Anne Frank’s room and their own room or verbally explain how Anne Frank’s living conditions would feel for them. For the control condition, students did not engage in a subsequent activity. Based on generative learning theory, we predicted that students engaging in generative learning activities would display higher posttest scores in knowledge and perspective taking than the control group. No such effects were found. Although the VR experience itself increased the ability to empathize with Anne Frank across all groups, it did not contribute to knowledge building. The study results indicate that even without any additional activity, VR can convey highly emotionally engaging testimonies and enables role taking, which suggests that VR is in particular suitable for affective learning.